The Merit of Using the Case Method in Teaching the Specialized Accounting Course. - Pointer, Larry Gene; Ljungdahl, Philip W. (The Accounting Review, 1973)
This article discusses the advantages of using the case method in teaching accounting course. The case method has several advantages, particularly in attracting and holding the interest of the non business major. The case method means something different to everyone claiming to use it. In this situation, it refers, in part, to the instructor's efforts to organize the class work so that a high level of student participation was encouraged. Rather than continue the question and answer technique of instructor and student, an attempt was made to develop formats for a series of discussions. Readings from a newly adopted textbook and business periodicals, such as Fortune and Forbes, were selected and organized into four modular time segments. Case studies, placed near the beginning of each module, were selected on the basis of their relevance to the main issue considered in the module, and upon the setting of the case. A considerable effort was made to use cases in which a technologically oriented company operating in the Southwest needed to make difficult decisions based in part on accounting financial data.